Clinical Significance of Histological Effect and Intratumor Stromal Expression of Tenascin-C in Resected Specimens After Chemoradiotherapy for Initially Locally Advanced Unresectable Pancreatic Ductal Adenocarcinoma. Issue 4 (April 2018) - Hayasaki, Aoi; Murata, Yasuhiro; Usui, Masanobu; Hibi, Taemi; Ito, Takahiro; Iizawa, Yusuke; Kato, Hiroyuki; Tanemura, Akihiro; Azumi, Yoshinori; Kuriyama, Naohisa; Kishiwada, Masashi; Mizuno, Shugo; et al.
Abstract : Objectives: Tenascin-C (TN-C) is an extracellular matrix protein that is up-regulated in pancreatic ductal adenocarcinoma (PDAC) stroma and associated with tumor invasion. We examined intratumor stromal expression of TN-C in resected specimens and the histologic effect of chemoradiotherapy (CRT) as prognostic indicators in initially locally advanced unresectable (UR-LA) PDAC. Methods: Among 110 UR-LA PDAC patients enrolled in the CRT protocol from February 2005 to December 2015, 46 who underwent curative-intent resection were classified as high (tumor destruction >50%) and low (⩽50%) responders according to the Evans grading system. Tenascin-C expression was immunohistologically evaluated in all patients except one with complete response. Results: The 12 high responders achieved a significantly higher R0 rate than did the 34 low responders (83.3 vs 47.1%), but disease-specific survival (DSS) time was not significantly different (median survival time, 29.8 vs 21.0 months). Tenascin-C expression was inversely correlated with histologic effect of CRT. The 22 patients with negative TN-C had significantly longer DSS time than did the 23 with positive TN-C (29.3 vs 17.1 months). In multivariate analysis, only TN-C expression was a significant prognostic factor for DSS. Conclusions: Intratumor stromal expression of TN-C is a strong prognostic indicator in UR-LA PDAC patients with resection after CRT. Abstract : Supplemental digital content is available in the text.